2023
DOI: 10.3389/fpubh.2023.1151999
|View full text |Cite
|
Sign up to set email alerts
|

Effect of COVID-19 vaccination on the outcome of in vitro fertilization: A systematic review and meta-analysis

Abstract: BackgroundUniversal COVID-19 vaccination programs are now recommended in several countries and represent the most effective preventive measure against COVID-19. However, some reports suggest that vaccination may cause infertility or have adverse effects on pregnancy. Conflicting reports have led to vaccine hesitancy in women planning pregnancy.PurposeTo determine whether vaccination against COVID-19 affects in vitro fertilization (IVF) outcomes, we conducted a meta-analysis.MethodA systematic search was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…At present, the evidence is rapidly growing that the coronavirus vaccination itself cannot be directly and biologically linked to the decline in births and fertility (Wang et al, 2023; Zaçe et al, 2022). This unanimous opinion is supported by a growing number of studies with different designs and on male and female fertility (Aharon et al, 2022; Ba et al, 2023; Barda et al, 2022; Gonzalez et al, 2021; Morris, 2021; Reschini et al, 2022; Yang et al, 2023; Yildiz et al, 2023) and miscarriage (Yland et al, 2023; Zauche et al, 2021), including already some review articles (Rimmer et al, 2023; Wesselink et al, 2022; Zhang et al, 2023; Zhu et al, 2023). Several studies report changes in the duration of menstrual cycle length following COVID-19 vaccination (Alvergne et al, 2023), but these changes are small (+/-1 day) and resume in the next cycle, thus not threatening fertility (Alvergne, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…At present, the evidence is rapidly growing that the coronavirus vaccination itself cannot be directly and biologically linked to the decline in births and fertility (Wang et al, 2023; Zaçe et al, 2022). This unanimous opinion is supported by a growing number of studies with different designs and on male and female fertility (Aharon et al, 2022; Ba et al, 2023; Barda et al, 2022; Gonzalez et al, 2021; Morris, 2021; Reschini et al, 2022; Yang et al, 2023; Yildiz et al, 2023) and miscarriage (Yland et al, 2023; Zauche et al, 2021), including already some review articles (Rimmer et al, 2023; Wesselink et al, 2022; Zhang et al, 2023; Zhu et al, 2023). Several studies report changes in the duration of menstrual cycle length following COVID-19 vaccination (Alvergne et al, 2023), but these changes are small (+/-1 day) and resume in the next cycle, thus not threatening fertility (Alvergne, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a systematic review and meta-analysis published in April 2023 analyzed 18,877 individual cases undergoing IVF [ 64 ], vaccinated with either an mRNA or inactivated virus vaccine. Their results conclude that vaccination against COVID-19 did not adversely affect the different stages of the process (number of oocytes and MII/mature oocytes obtained; implantation, blastocysts, and fertilization rates) or the final outcome (biochemical pregnancy rates) of IVF.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a systematic meta-analysis shows no adverse effects of vaccination against SARS-CoV-2 on fertility, infertility, or the course of fertility treatment [ 22 ]. Another more recent meta-analysis of 20 studies with a total of 18,877 ART treatment cycles also showed no significant negative effects of vaccination against SARS-CoV-2 on treatment outcome compared with nonvaccinated women [ 23 ]. A population-based study of 18,780 women with miscarriages from the United Kingdom found no association of vaccination with miscarriages compared with unvaccinated women before the pandemic (adjusted odds ratio of 1.02, 95% CI of 0.96–1.09 [ 24 ]).…”
Section: Discussionmentioning
confidence: 99%